Oral health attitudes and risk behaviors in nursing students - Dias, Inês; Albuquerque, Carlos; Cunha, Madalena; Dias, António; Dias, Ana Rita (Millenium - Journal of Education, Technologies, and Health, 2020)
Introduction: Tendency, the citizens are more concerned with their physical health in general than with oral health. Therefore, nurses are often health professionals who have the first contact with patients with dental problems. They also become privileged agents in promoting oral health and preventing oral diseases. Objetives: Evaluate oral health attitudes and behaviors in nursing students and relate them to risky behaviors for cavities and periodontal disease (smoking and alcoholic habits and consumption of sugary foods and drinks). Methods: Cross-sectional study with a convenience sample of 289 nursing students who attended Health School of Centre Region. Data collection was carried out through a self-administered questionnaire on oral health attitudes and behaviors, which included the Hiroshima University Dental Behavior Inventory (HUDBI). Results: The average of HUDBI score was 7.3 ± 1.2 and the students who consumed alcohol “every week”, smoked, consumed sugary foods and drinks “sometimes” and made this consumption after meals tend to have better global values of HUDBI. Conclusion: The results are consistent with national and international research, confirming that the attitudes and behaviors of nursing students regarding oral health are adequate. There was no evidence of an impacting relationship between attitudes and behaviors of oral health in risk behaviors for dental caries and periodontal disease.